Biostratigraphy, palaeoenvironments and palaeogeography of the Cretaceous–Paleogene succession in the Oudiksou Basin, Central Middle Atlas of Morocco - Abdessamad Amelieh; Mostafa Oukassou; Guillaume Guinot; Omar Zafaty; Hicham Si Mhamdi; Johan Yans; André Charrière; Rodolphe Tabuce (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Evolution of dietary preferences of the Lophiodontidae (Mammalia, Perissodactyla) from Southern France - Manon Hullot; Céline Robinet; Quentin Vautrin; Rodolphe Tabuce; Pierre-Olivier Antoine; Gildas Merceron; Fabrice Lihoreau (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

New insights into the diversity of strepsirrhine primates from the late early–early middle Eocene of North Africa (Algeria and Tunisia) - Laurent Marivaux; Anne-Lise Charruault; Mohammed Adaci; Mustapha Bensalah; Mahammed Mahboubi; Fateh Mebrouk; Hayet Khayati Ammar; El Mabrouk Essid; Wissem Marzougui; Rim Temani; Rodolphe Tabuce (Journal of Human Evolution, 2025)

Abrupt changes in continental sedimentation triggered by monsoon-type event during EECO hyperthermals, Minervois Basin, Southern France - Cindy BOYRIE; Flavia GIRARD; Johan YANS; Grégory BALLAS; Fabrice LIHOREAU; Mouloud BENAMMI; Hélène BOURGET; Géraldine GARCIA; Christine LEREDDE; Aimée PELLISSIER-TANON; Xavier VALENTIN; Dominique VIDALENC; et al. (Sedimentary Geology, 2025)

Impact of the EECO on mammalian faunas: New Ypresian localities from Montpellier (France), a multidisciplinary approach - Fabrice Lihoreau; Johan Yans; Mouloud Benammi; Flavia Girard; Gregory Ballas; Hélène Bourget; Cindy Boyrie; Jacinthe Caillaud; Anne-Lise Charruault; Killian Gernelle; Floréal Solé; Xavier Valentin; et al. (Proceedings of the Geologists' Association, 2025)

Taxonomy and evolutionary history of peradectids (Metatheria): New data from the early Eocene of France - Killian Gernelle; Guillaume Billet; Emmanuel Gheerbrant; Marc Godinot; Bernard Marandat; Sandrine Ladevèze; Rodolphe Tabuce (Journal of Mammalian Evolution, 2024)

A new primate community from the earliest Oligocene of the Atlantic margin of Northwest Africa: Systematic, paleobiogeographic, and paleoenvironmental implications - Laurent Marivaux; Mohamed Benammi; Lahssen Baidder; Omar Saddiqi; Sylvain Adnet; Anne-Lise Charruault; Rodolphe Tabuce; Johan Yans; Mouloud Benammi (Journal of Human Evolution, 2024)

A new stegosaurian dinosaur (Ornithischia: Thyreophora) with a remarkable dermal armour from the Middle Jurassic of North Africa - Omar Zafaty; Mostafa Oukassou; Facundo Riguetti; Julio Company; Saad Bendrioua; Rodolphe Tabuce; André Charrière; Xabier Pereda-Suberbiola (Gondwana Research, 2024)

Integrated remote sensing data and field investigations for geological mapping and structural analysis. The case of SW Tichoukt ridge (Middle Atlas, Morocco) - Omar Zafaty; Mostafa Oukassou; Hicham Si Mhamdi; Rodolphe Tabuce; André Charrière (Journal of African Earth Sciences, 2023)

Earliest Embrithopod Mammals (Afrotheria, Tethytheria) from the Early Eocene of Morocco: Anatomy, Systematics and Phylogenetic Significance - Emmanuel Gheerbrant; Fatima Khaldoune; Arnaud Schmitt; Rodolphe Tabuce (Journal of Mammalian Evolution, 2021)

Incisor Enamel Microstructure of Hystricognathous and Anomaluroid Rodents from the Earliest Oligocene of Dakhla, Atlantic Sahara (Morocco) - Laurent Marivaux; Myriam Boivin; Sylvain Adnet; Mohamed Benammi; Rodolphe Tabuce; Mouloud Benammi (Journal of Mammalian Evolution, 2019)

Taxonomic review of the “Bulimes”, terrestrial gastropods from the continental Eocene of the Hamada de Méridja (northwestern Sahara, Algeria) (Mollusca: Stylommatophora: Strophocheilidae?), with a discussion of the genera of the family Vidaliellidae - Sid Ahmed Hammouda; Dietrich Kadolsky; Mohammed Adaci; Fateh Mebrouk; Mustapha Bensalah; M’hammed Mahboubi; Rodolphe Tabuce (PalZ, 2017)

Tooth Enamel Microstructure of Living and Extinct Hyracoids Reveals Unique Enamel Types Among Mammals - Rodolphe Tabuce; Erik R. Seiffert; Emmanuel Gheerbrant; Léanie Alloing-Séguier; Wighart von Koenigswald (Journal of Mammalian Evolution, 2017)

The early evolutionary history of anomaluroid rodents in Africa: new dental remains of a zegdoumyid (Zegdoumyidae, Anomaluroidea) from the Eocene of Tunisia - Laurent Marivaux; El Mabrouk Essid; Wissem Marzougui; Hayet Khayati Ammar; Gilles Merzeraud; Rodolphe Tabuce; Monique Vianey‐Liaud (Zoologica Scripta, 2015)
The Late Early‐to‐Early Middle Eocene Zegdoumyidae are the oldest representatives of the order Rodentia to be known in Africa thus far. Despite the fragmentary nature of their fossil record, these early African rodents have been central in discussions surrounding the early evolutionary history of the Anomaluroidea clade (the living forms of which are the ‘scaly‐tailed squirrels’, i.e. Anomaluridae). Here, we describe new dental remains attributable to Zegdoumys sbeitlai , a zegdoumyid from Tunisia (Djebel Chambi, CBI ‐1) dated at ca 50–45 Ma. The original material referred to this taxon was limited to four teeth documenting few dental loci. The new gathered material comprises practically all dental loci (except P4), thereby allowing a better description and characterization of this taxon. This Tunisian species is clearly distinct from its roughly coeval Algerian counterpart ( Z. lavocati ) or from the younger species recorded from Namibia ( Z. namibiensis ). We investigated the phylogenetic positions of Z. sbeitlai and the Zegdoumyidae in a high‐level rodent phylogeny with a cladistic assessment of the dental evidence. Our results show that zegdoumyids represent the earliest offshoots (pectinately arranged) of a large clade that also encompasses the more advanced Eocene anomaluroids (here named Nementchamyidae), the Miocene Nonanomaluridae, and the stem and crown Anomaluridae. In this phylogenetic context, the species of Zegdoumys are the basalmost members of this large Anomaluroidea clade. Zegdoumyid taxa are therefore the oldest stem anomaluroid candidates, a statement which strengthens support for the hypothesis of the great antiquity of the Anomaluroidea clade in Africa. From a historical biogeography perspective, this assumption suggests that anomaluroids invaded Asia from Afro‐Arabia sometime during the Middle Eocene, a dispersal event which was likely concomitant but opposite to the dispersals envisaged for the hystricognathous rodents and anthropoid primates from Asia to Afro‐Arabia.

Petrosal and Bony Labyrinth Morphology Supports Paraphyly of Elephantulus Within Macroscelididae (Mammalia, Afrotheria) - Julien Benoit; Nick Crumpton; Samuel Merigeaud; Rodolphe Tabuce (Journal of Mammalian Evolution, 2014)

A Phororhacoid bird from the Eocene of Africa - Cécile Mourer-Chauviré; Rodolphe Tabuce; M’hammed Mahboubi; Mohammed Adaci; Mustapha Bensalah (The Science of Nature, 2011)

The oldest African bat from the early Eocene of El Kohol (Algeria) - Anthony Ravel; Laurent Marivaux; Rodolphe Tabuce; Mohammed Adaci; Mohammed Mahboubi; Fateh Mebrouk; Mustapha Bensalah (The Science of Nature, 2011)

A structural intermediate between triisodontids and mesonychians (Mammalia, Acreodi) from the earliest Eocene of Portugal - Rodolphe Tabuce; Julien Clavel; Miguel Telles Antunes (The Science of Nature, 2011)